Villain - Shuichi Yoshida 1968-; Philip Gabriel 1953- (UK Vintage Books, 2011)
"January 6, 2002. The body of a female insurance saleswoman is found in the southernmost region of Japan, at a spot rumored to be a home to ghosts. Shortly thereafter Yuichi, a young construction worker, is arrested by the Nagasaki police on suspicion of murder..."--from publisher description
Everyone Has Something to Hide . The Japanese Crime-Writing Sensation
"Originally published in Japan as Akunin by Asahi Shimbun Publication Inc., Tokyo, in 2007"--T.p. verso
Keywords: Literature (3GdCOHs; Murder -- Investigation -- Fiction -- Japan -- Nagasaki-shi -- Murder -- Investigation -- Fiction; General; Fugitives from justice -- Fiction; Marginality, Social -- Japan -- Fiction